PLEONASM IN THE TV SERIES THE WALKING DEAD - Fitriansyah, Innu; Rosmaidar, Rosmaidar (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2018)
This study aimed at finding and identifying the types and functions of pleonasms occurred in the TV series The Walking Dead. The object of this study was the 10 episodes of The Walking Dead from season 7. This is a qualitative descriptive research, since it involves the utterances of characters in the film that need to be summarized and described. The data were collected using the documentation technique. Some steps were taken in the process of collecting and analyzing the data, such as extracting the subtitles, watching the series, converting, printing and reading the subtitles, finding and marking the pleonastic expressions, and identifying the types, the sub-types, and the functions of pleonasms. 165 pleonastic expressions were found in the series. Out of 165.89 (54%) is syntactic pleonasms, and 76 (46%) is semantic pleonasms. A total of 97 (59%) pleonastic expressions function were highly to emphasize or intensify the expressions, which holds the majority.